A Positive Employee Experience: An Approach from Recruitment to Retention - Srinivasaiah, Bharath (Journal of Global Economy, Business and Finance, 2024)
This study aims to examine the formation and maintenance of positive employee experience, the way employees see the organization through its all touchpoints starting from the recruitment process to their exit, proposing an integrated approach to Employee Experience (EX) optimization. The research employs a comprehensive analysis of five key EX stages and explores strategies for their integration. The findings reveal the interconnectedness of EX stages and highlight three critical areas for improvement: experience personalization, fostering a continuous learning culture, and technology implementation. The study proposes a conceptual model for EX optimization, emphasizing the need for a systemic approach that aligns EX initiatives across all employee lifecycle stages. The research contributes to the field by offering a novel integrated framework that goes beyond traditional HR management, positioning EX as a strategic imperative for organizational success. This approach provides organizations with a roadmap for creating outstanding employee experiences, potentially leading to enhanced competitiveness in talent attraction, development, and retention.